Dyadic support across contraceptive decision-making among young adult breast cancer survivors and their partners. Issue 6 (2nd November 2022) - Smith, Ellie; Drizin, Julia H.; Harvey, S. Marie; Gorman, Jessica R.
Abstract: Objective: The purpose of this study is to explore the role of dyadic support across the contraceptive decision-making process between young adult breast cancer (YABC) survivors and their partners. Research Approach: Semi-structured interviews with YABC survivors and their partners. Participants: Twenty-five young adult breast cancer survivors and their partners ( n = 50). Survivors reported an average age of 36.9 years ( SD = 4.30) and the majority self-identified as white (86.2%). Methodological Approach: Thematic analysis approach with dyads as the primary unit of analysis, guided by the dyadic decision-making framework and the Theory of Gender and Power. Results: Perceived lack of contraceptive options due to a history of hormone-sensitive cancer, perceived infertility, and contraception as a result of cancer treatment (e.g., hysterectomy) contributed to the contraceptive decision context for survivors and their partners. Contraceptive support varied across couples depending on the cancer-specific context, where communication, sharing responsibility, and respecting bodily autonomy revealed as supportive behaviors. Other social influences including survivors' desire to conceive biologically and family planning desires also related to partner supportive behaviors. Interpretations: YABC survivors face specific challenges to contraceptive decision-making where partners can offer supportive behaviors. Health care providers can also support couples by engaging in triadic communication about contraception and family planning. Implications for Psychosocial Providers or Policy: Psychosocial providers can support couples by encouraging them to talk together about contraception and highlighting the importance of triadic communication with a healthcare provider to support shared decision-making and alignment of contraceptive decisions with family planning desires.